Batas Usia Perkawinan: Tantangan Hukum dan Solusi Implementasi Undang-Undang Nomor 16 Tahun 2019 - Madani Ibnu Usman, MA. (Zaaken: Journal of Civil and Business Law, 2025)
Early marriage in Indonesia is a complex issue influenced by various legal, cultural, and social factors. This study identifies the legal challenges in implementing marriage age limits, including regulatory disharmony and the high number of marriage dispensations. Additionally, cultural norms and social practices in various regions, such as Madura and Tana Toraja, contribute to this phenomenon by creating social pressures that encourage early marriage. The methodology used in this research includes secondary data analysis from government reports and case studies in several areas. The conclusion indicates that collaborative efforts between the government, society, and related institutions are necessary to raise legal awareness and reduce the incidence of early marriage. Education and strict law enforcement are key to protecting the rights of children and women and creating a better environment for future generations.